Who identifies with the "Russian World"? Geopolitical attitudes in southeastern Ukraine, Crimea, Abkhazia, South Ossetia, and Transnistria. Issue 6 (1st November 2016) - O'Loughlin, John; Toal, Gerard; Kolosov, Vladimir
Abstract: The concept of the Russian world ( Russkii mir ) re-entered geopolitical discourse after the end of the Soviet Union. Though it has long historical roots, the practical definition and geopolitical framing of the term has been debated and refined in Russian political and cultural circles during the years of the Putin presidency. Having both linguistic-cultural and geopolitical meanings, the concept of the Russian world remains controversial, and outside Russia it is often associated with Russian foreign policy actions. Examination of official texts from Vladimir Putin and articles from three Russian newspapers indicate complicated and multifaceted views of the significance and usage of the Russkii mir concept. Surveys in December 2014 in five sites on the fringes of Russia – in southeastern Ukraine, Crimea, and three Russian-supported de facto states (Abkhazia, South Ossetia, and Transnistria) – show significant differences between the Ukrainian sample points and the other locations about whether respondents believe that they live in the Russian world. In Ukraine, nationality (Russian vs. Ukrainian) is aligned with the answers, while overall, attitudes toward Russian foreign policy, level of trust in the Russian president, trust of Vladimir Putin, and liking Russians are positively related to beliefs about living in the Russian world. In Ukraine, the negative reactions to geopolitical speech acts and suspicions about Russian government actions overlap with and confuse historical linguistic-cultural linkages with Russia, but in the other settings, close security and economic ties reinforce a sense of being in the Russian "world."